Integrated Transceivers for Emerging Medical Ultrasound Imaging Devices: A Review - Chen, Chao; Pertijs, Michiel A. P. (IEEE open journal of solid-state circuits, 2021)
As medical ultrasound imaging moves from conventional cart-based scanners to new form factors such as imaging catheters, hand-held point-of-care scanners and ultrasound patches, there is an increasing need for integrated transceivers that can be closely integrated with the transducer to provide channel-count reduction, improved signal quality and even full digitization. This paper reviews compact and power-efficient circuit solutions for such transceivers. It starts with a brief overview of ultrasound transducer technologies and the operating principles of the ultrasound transmit-receive signal path. For transmission, high-voltage pulsers are reviewed, from compact unipolar pulsers to multi-level pulsers that provide amplitude control and improved power efficiency. The review of receive circuits starts with low-noise amplifiers as the power- and performance-limiting building block. Solutions for time-gain compensation are discussed, which are essential to reduce signal dynamic range by compensating for the decaying echo-signal amplitude associated with propagation attenuation. Finally, the option of direct digitization of the echo signal at the transducer is discussed. The paper ends with a reflection on future opportunities and challenges in the area of integrated circuits for ultrasound applications.